Anti-MDA5 antibody-positive dermatomyositis: pathogenesis and clinical progress - Lu, Xin; Peng, Qinglin; Wang, Guochun (Nature reviews. Rheumatology, 2024)
Anti-melanoma differentiation-associated protein 5 (MDA5) antibody-positive dermatomyositis (MDA5-DM) is a subtype of dermatomyositis. Although the aetiology and pathology remain unclear, increasing evidence suggests that viral infection is a potential trigger of MDA5-DM. Multiple factors, including T cells, B cells, neutrophils and macrophages, are implicated in the pathophysiology of MDA5-DM. Distinctive skin rashes, rapidly progressive interstitial lung disease, peripheral lymphopenia and elevated serum ferritin levels are the most prominent clinical and laboratory features of MDA5-DM. Concomitant infection is a common complication of MDA5-DM. The proper evaluation of patients with MDA5-DM requires knowledge of the disease heterogeneity and clinical course variability. Several biomarkers, including serum levels of anti-MDA5 antibodies and biomarkers related to macrophage activation, have been identified as useful tools for monitoring disease activity and prognosis. MDA5-DM shows a poor response to conventional glucocorticoid and immunosuppressant therapy and has a poor overall prognosis. Therefore, there is an urgent need to explore the key pathogenic mechanisms of MDA5-DM and develop novel therapeutic options for patients. This Review discusses recent clinical progress and pathogenic findings of MDA5-DM.